PENINGKATAN KAPASITAS ANGGOTA KELOMPOK PETANI PRODUSEN GARAM BAHARI MEUGAHNA - Baihaqi Baihaqi; Syifa Saputra; Aidil Amar; Afkar Afkar; Faizin Faizin; Fina Meilinar (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2024)
The main focus of implementing this community service activity is to increase the human resource capacity of Salt Farmers in Bluka Teubai Village which aimed to provide knowledge and skills in the form of training in business management, marketing, packaging and improving product quality. After the activities were carried out, it is hoped that the salt farmer group will be able to develop their business more effectively and efficiently, increase productivity and business competitiveness, and improve the economic welfare of the group and the surrounding community. Based on the results of the PKM activities that have been implemented, it can be seen that there has been an increase in the capacity and skills of the Meugahna Marine Salt Farmers Group's human resources in various aspects related to marine salt farming, such as business management, marketing and improving product quality. Apart from that, developing entrepreneurship in the salt farming sector can also help increase income, thereby encouraging local economic development and the welfare of the surrounding community.